Teungku Abdul Djalil: Political Hack “Hakko Ichiu” and Founder of the Indonesian Opposition to the Japanese Occupation - Kamza, Muhjam; Kusnafizal, Teuku; Yusrizal, M; Yanti, Ulfa (SCAD Independent, 2023)
Diplomacy and war brought independence to Indonesia. Many people joined in the battle for independence, even Muslim scholars and students interested in expelling colonialism. Teungku Abdul Djalil, a preacher in Aceh, issued a fatwa commanding the people to “depopulate” the Japanese from the veranda of Mecca. Teungku Abdul Djalil, or more generally known as Teungku Cot Plieng, was the leader of Dayah Cot Plieng in Bayu, North Aceh. Since 1942, this prominent clergyman has rallied 400 students (santri) to openly oppose the Japanese resistance in Aceh. His study attempted to quantify the success of the character and his followers (santri) in achieving Indonesian independence, as well as their resolve not to be influenced by Japanese Hakko Ichiu political propaganda. Utilizing a descriptive-analytic historical method, the research process began with data collection (heuristics), source critique, interpretation, and historiography. The research subjects’ credibility was established through perpetrators and witnesses from Japan’s history of resistance. This investigation revealed that Teungku Abdul Djalil and his students played an important role as the first pioneers in expelling the Japanese from Indonesia.